The COMPARISON OF SHARIA AUDITING AND SHARIA ACCOUNTING IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Hisam Ahyani (OIKONOMIKA : Jurnal Kajian Ekonomi dan Keuangan Syariah, 2021)
This research is based on the neglect and lack of socialization of sharia auditing and sharia accounting in an era that is all digital like today. The purpose of this research is to determine the extent of the urgency of sharia auditing and accounting if it is applied in Indonesia, especially in the era of disruption like today, where the current era of disruption has created a separate challenge from the existence of sharia audits and operations which continue to experience developments in the scope of the sharia economy. especially in Indonesia. The research method used in scientific research is literature review by reviewing literature (books and journals and other articles) that support the themes to be discussed (sharia auditing and accounting). The nature of this research is descriptive-analytic using qualitative data analysis. This study resulted in the finding that the urgency of sharia auditing is needed, especially in Islamic banks or non-bank institutions such as LKS (Islamic financial institutions) in Indonesia. Sharia accounting is needed in order to increase the branding value of a company from the accounting system used to ensure the superiority of a bank or Islamic financial institution in Indonesia, especially in the era of disruption (industrial era 4.0) as it is today.